Creation of final year project administration system using php script and MySQL - Yusnita Halim; Afsal Abdullah; Sharifah Nurulhuda Tuan Mohd Yasin (RedWhite Press, 2022)
This research describes the development of the Final Year Project (FYP) Management System, which aims to provide an efficient way to manage the FYP for students of Politeknik Kuala Terengganu (PKT). The problem is that there are no organized and systematic FYP records and reports that the coordinator of FYP can manage in PKT. Further, no platform is provided to store and access FYP reports that students have documented resulted in difficulty for reading and reference purposes. There are two objectives for this project. First, to develop a management system and data storage related to the FYP online more systematically. Second, to facilitate the FYP coordinator, supervisors and students to access information on FYP more quickly and accurately. This research has succeeded in its goal by implementing the V-Model methodology as a framework for system development with PHP script and MySQL as the database. In conclusion, this research has succeeded in its goals by making it easier for users to manage and access previous FYP report by offering an online smart archive system.